Targeting tumour-related alternative splice variant RAC1B with anti-sense oligonucleotides - Bessa, Cláudia (2022)
Over 90% of human protein coding genes are able to generate more than one transcript due to alternative splicing. In cancer, certain alternative splicing variants are frequently overexpressed and contribute to tumour progression and aggressiveness. This is well illustrated by RAC1B, a variant of the small GTPase RAC1 that is overexpressed in tumours from colon, breast, lung, pancreas and thyroid. RAC1B is generated by inclusion of alternative exon 3b and the resulting protein contains 19 additional amino acids, which alter regulation and signalling properties. In colorectal cancer, RAC1B is overexpressed in the subgroup of BRAF mutated tumours. Using HT29 cells as a model, RAC1B was shown to exist predominantly in the active GTP-bound conformation in cells and signal via NF-κB to sustain tumour cell survival. To exploit the suitability of this highly gene-specific event for oligonucleotide-based therapeutic intervention, we tested different anti-sense oligonucleotides to interfere with RAC1B expression levels in cancer cells. We found that synthetic siRNAs that induced transcript degradation were able to efficiently suppress RAC1B transcript and protein levels in cells. Phosphorodiamidate morpholino-modifed oligonucleotides (PMO, morpholinos) present higher affinity and stability than conventional oligonucleotides. Thus, a morpholino was designed that targets the intron3–exon3b splice junction including the exonic splice enhancer sequence for SRSF1 binding that we previously identified. When validated in HT29 colorectal tumour cells, this morpholino performed poorly on levels of RAC1B transcript or protein and did not affect RAC1B-dependent cell viability. Indeed, morpholinos do not easily enter mammalian cells in culture but have shown efficacy in animal models in vivo and in human clinical trials. In order to validate, whether the morpholino’s target sequence was able to mediate RAC1B inhibition, we employed the nuclease resistant 2′-O-methyl-modified (2OM) oligonucleotides directed to this and three other exon 3b sequences. We found that all four 2OM oligos reduced RAC1B transcript and protein, comparable to the efficiency of the synthetic siRNA and sustained the downregulating effect for up to 72 h post-transfection.